Fused bi-heteroaryl substituted hydantoin compounds as TACE inhibitors. Issue 14 (15th July 2017) - Tong, Ling; Kim, Seong Heon; Rosner, Kristin; Yu, Wensheng; Shankar, Bandarpalle B.; Chen, Lei; Li, Dansu; Dai, Chaoyang; Girijavallabhan, Vinay; Popovici-Muller, Janeta; Yang, Liping; Zhou, Guowei; et al.
Graphical abstract: Abstract: We have identified a series of hydantoin-derived TNF-a converting enzyme (TACE) inhibitors containing a pendant fused bi-heteroaryl group, which demonstrate sub-nanomolar potency (Ki), excellent activity in human whole blood assay, and improved DMPK profiles over prior series.